Agantuk [videorecording (DVD)] = The stranger - Ray, Satyajit, 1921-1992; Datta, Utpal; Shankar, Mamata; Dey, Dipankar; Ghosha, Rabi, 1931-1997; Chatterjee, Subrata; Chatterjee, Dhritiman, 1945- (Eclipse. Series 40, Late Ray., 2014)
A wise and witty world traveler returns to Calcutta after 35 years to visit his niece, who had only briefly known him as a child. She accepts the stranger's story, but her suspicious husband believes the long-lost uncle is an imposter who has come to claim an inheritance.